Sustainable Educational Innovation: Contextualizing Ibn Sina’s Philosophical Framework in Modern Kuttab - Basyir Yaman; Toto Suharto; Yusup Rohmadi; Luthfi Muhyiddin; Muhammad Khoirul Malik (Universitas Muhammadiyah Surakarta, 2024)
Objective: This research aims to reconstruct Ibn Sina's thoughts on basic education through kuttab institutions, and examine its relevance to the development of Islamic educational institutions in Indonesia within the framework of the Sustainable Development Goals (SDGs). Theoretical framework: The theoretical framework of this research uses an approach to Islamic education philosophy, especially Ibn Sina's thoughts on the purpose of education, the stages of learning, and the role of kuttab institutions as the foundation of character and intellectual education. The literature studied includes Ibn Sina's classic works such as Al-Siyasah and Al-Najat, as well as the results of contemporary research on the implementation of Islamic education based on philosophical and spiritual values. Literature review: The main focus is on how the concept of basic education in Ibn Sina's thought can be used as an alternative model to strengthen the quality of Islamic basic education that is inclusive, equitable, and sustainable in Indonesia. Methods: The research method used is a qualitative approach with the type of library research, with content analysis techniques and critical interpretation of primary and secondary texts. Data were collected through a literature review and analyzed hermeneutically. Results: The results of the study show that Ibn Sina's thoughts on kuttab emphasize the importance of morality-based education, intellectuality, and personalization of methods according to the stage of child development. This model is in line with the SDGs indicators, especially the 4th (quality education), 10th (reducing inequality), and 16th (peace, justice, and resilient institutions). Implications: The implication of this study is the need to revitalize Islamic basic education institutions such as kuttab that are oriented to local values and classical philosophies that are relevant to global challenges. Novelty: The novelty of this research lies in the integration of Ibn Sina's classical thought with the paradigm of sustainable development, which has not been widely explored in the study of contemporary Islamic education in Indonesia.